Lean Supply Chain Management Practices and Performance: Empirical Evidence from Manufacturing Companies - Haifa Abu Nimeh; Ayman Bahjat Abdallah; Rateb Sweis (International Journal of Supply Chain Management, 2018)
The current study aims to investigate the effect of lean supply chain management practices on supply chain performance and market performance in manufacturing companies in Jordan. Five lean supply chain management practices were identified based on an extensive literature review, just-in-time system, flow of information, supplier relationship, customer relationship, and waste reduction. To achieve the study goals, a survey questionnaire was prepared and distributed to managers of 400 manufacturing companies from different sectors and sizes. The final number of returned usable questionnaires was 308, representing a response rate of 77%. The results revealed positive and significant effects of three lean supply chain management practices on market performance, namely, JIT system, flow of information, and customer relationship. In addition, all lean supply chain management practices showed positive and significant effects on supply chain performance. Furthermore, supply chain performance demonstrated a positive and significant effect on market performance.